Ethnic Enclosure in Multicultural Muslim Community Life: Case Study in Golestan Province, I.R. Iran - Reza Saberi (Jurnal Studi Sosial dan Politik, 2019)
In this paper we focus on ethnicity and ethnic enclosure among Muslim ethnic groups in Golestan province of Iran. It also has referred to the aspects of interethnic interactions among and between the ethnic groups which consider themselves, and are regarded by others, as being culturally distinctive. We find that ethnic differences and similarities have made individuals ethnically consciousness. This in turn has implications for and influence ethnic enclosure. People in the cities were socially organized mostly along some aspects of ethnicity such as ethnic identities based on linguistic, religious sect (Shiite and Sunnite) or region of origin criteria. People grew strongly self-consciousness of their ethnic identity under these circumstances of contact with members of other groups. They develop standardized ways of behaving vis-à-vis each other, and orient themselves socially according to ‘ethnic map’. Ethnic groups model settlement pattern, marriages and perceptions along ethnic lines, and ethnic disparities come in to play while interacting with out-group members.